What can implementation science offer civil society in their efforts to drive rights-based health reform? - Diya Uberoi; Tolulope Ojo; Abi Sriharan; Lincoln Lau (BMC, 2023)
Abstract Over the years, civil society organizations (CSOs) have made tremendous efforts to ensure that state policies, programmes, and actions facilitate equitable access to healthcare. While CSOs are key actors in the realization of the right to health, a systematic understanding of how CSOs achieve policy change is lacking. Implementation science, a discipline focused on the methods and strategies facilitating the uptake of evidence-based practice and research can bring relevant, untapped methodologies to understand how CSOs drive health reforms. This article argues for the use of evidence-based strategies to enhance civil society action. We hold that implementation science can offer an actionable frame to aid CSOs in deciphering the mechanisms and conditions in which to pursue rights-based actions most effectively. More empirical studies are needed to generate evidence and CSOs have already indicated the need for more data-driven solutions to empower activists to hold policymakers to account. Although implementation science may not resolve all the challenges CSOs face, its frameworks and approaches can provide an innovative way for organizations to chart out a course for reform.